1999
DOI: 10.1095/biolreprod61.4.955
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Estrogen Receptors α and β in the Rat Uterus1

Abstract: The uterus is an important target organ for steroid hormones. The effects of these hormones are mediated via specific receptors. The aim of this study was to compare the expression, distribution, and regulation of estrogen receptor (ER) alpha and beta in the rat uterus in order to establish possible different biological roles for the two receptor forms. Ovariectomized rats were treated with either estradiol (E(2)), progesterone (P(4)), or combinations of these for 24 or 48 h. The mRNA levels were measured by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
96
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 48 publications
(81 reference statements)
16
96
1
1
Order By: Relevance
“…In mammals, two nuclear receptors mediate the actions by stimulating the binding of estrogen, the α-and β-estrogen receptors, having the predominance of α-estrogen receptors in the uterus (Klinge 2001, Nilsson et al 2001, Wang et al 1999. This also reflects in higher affinity of the metabolite α-zearalenol to bind estrogen receptors (Takemura et al 2007) and greater susceptibility of pigs to the effects of ZEA by the predominance in the production of this metabolite (Malekinejad et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, two nuclear receptors mediate the actions by stimulating the binding of estrogen, the α-and β-estrogen receptors, having the predominance of α-estrogen receptors in the uterus (Klinge 2001, Nilsson et al 2001, Wang et al 1999. This also reflects in higher affinity of the metabolite α-zearalenol to bind estrogen receptors (Takemura et al 2007) and greater susceptibility of pigs to the effects of ZEA by the predominance in the production of this metabolite (Malekinejad et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The recently discovered beta receptor (ER␤) is present at very low levels in the uterus, and it is not clear whether functional levels of ER␤ protein are present (43)(44)(45). Zhong and coworkers (41) also have demonstrated that nongenomic effects of E2 occur through ER␣ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Hiroi et al, 1999;Wang et al, 1999;Nephew et al, 2000) indicate that the dominant receptor subtype in the rat endometrium is ERα, which is localized in nuclei of the luminal and glandular epithelium and in the stroma. The effect of E 2 on uterine ER in OVX rats is apparently biphasic.…”
Section: Discussionmentioning
confidence: 99%